2020
DOI: 10.1177/0031512520969637
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Evaluation of Computer Icons: Visual Pattern Differences Between Art-Trained and Lay Raters of Icons

Abstract: Adopting eye-tracking measures, we explored the influence of art experience on the aesthetic evaluation of computer icons. Participants were 27 college students with art training and 27 laypersons. Both groups rated icons of varying complexity and symmetry for “beauty” while we recorded participants’ eye movements. Results showed that art-trained participants viewed the icons with more eye fixations and had shorter scanning paths than participants in the non-art group, suggesting that art-trained participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…This observation is corroborated by a report that observers viewing pre-reconstructive and post-reconstructive surgery images of patients with craniofacial anomaly tend to look less often and for less time at the anomalous side of the face compared with the nonanomalous side 45 . Apparent contradiction between “internal representation of beauty” theory and “beauty demands longer looks” must be viewed in the context that more eye fixation and shorter scanning paths are 2 different attributes of visual processing that are not necessarily mutually exclusive 46 …”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This observation is corroborated by a report that observers viewing pre-reconstructive and post-reconstructive surgery images of patients with craniofacial anomaly tend to look less often and for less time at the anomalous side of the face compared with the nonanomalous side 45 . Apparent contradiction between “internal representation of beauty” theory and “beauty demands longer looks” must be viewed in the context that more eye fixation and shorter scanning paths are 2 different attributes of visual processing that are not necessarily mutually exclusive 46 …”
Section: Discussionmentioning
confidence: 95%
“…45 Apparent contradiction between "internal representation of beauty" theory and "beauty demands longer looks" must be viewed in the context that more eye fixation and shorter scanning paths are 2 different attributes of visual processing that are not necessarily mutually exclusive. 46 Most confusing is probably the interpretation of visual gaze patterns of observers looking at human faces and understanding critical variables that influence the visual processing of faces with deformity. 42 There is general agreement that to immediately detect visible elements vital to initiate and maintain proper communication, esthetic judgment task about human faces reveals preference and proclivity to attributes of greater vitality value regardless of beauty characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 According to Shen et al, 24 participants performed significantly better when icons were more familiar (presented more frequently) during the visual search and semantic information recall tasks. Hu et al 26 hypothesized that art-trained participants had more eye gaze and shorter scan paths than those in the non-art group, suggesting that art-trained participants processed these icons more intentionally. Although the aforementioned researchers proposed that user familiarity can be enhanced through training, Huang et al 27 demonstrated that older adults still did not perform well when using the human-machine interface after receiving training.…”
Section: Principal Factors Affecting Icon Discriminationmentioning
confidence: 99%